Analysis of Determining The Cost of Replanting for Smallholder Oil Palm Plantations Using Annuities Model with Python - Rayyan Al Muddatstsir Fasa; Herlina Napitupulu; Sukono Sukono (Research Collaboration Community (RCC), 2023)
Palm oil replanting is a necessary activity to enhance the productivity of aging oil palm trees. However, the high costs associated with replanting often create a financial burden for farmers. To address this issue, the study proposes the implementation of a contribution or levy system for smallholder farmers while their oil palm plantations are still productive, which would alleviate the financial burden of replanting. The research methodology employed includes a literature review and primary data collection through a survey of smallholder farmers, with the data being processed to create a mathematical model and simulated using the Python programming language. The results of this study include the development of a mathematical model for the levy and distribution of replanting costs, along with a simulation of the proposed system. This model could help smallholder farmers prepare for replanting costs, enhance the sustainability of palm oil production, and ultimately increase productivity.